1996
DOI: 10.1002/pssb.2221940217
|View full text |Cite
|
Sign up to set email alerts
|

RES structure of Bi3+ centres in KCI: Bi, S and CaO:Bi crystals

Abstract: Emission, excitation, and polarization spectra as well as decay kinetics are studied at 4.2 to 500 K for the luminescence of BC' + centres in two crystals (KC1 and CaO) with strongly different electron-phonon interaction. It is concluded that three bands at -2.5, 3.11, and -1.5 eV, observed in the emission spectrum of the KC1 : Bi, S crystal belong to the same centre, but arise from states of different origin. The splitting of the 2.5 eV band, caused by the presence of a defect (S2-) near a Bi'+ ion is detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 13 publications
10
21
0
Order By: Relevance
“…Thus, the decay kinetics of the UV emissions of LuAG:Bi and YAG:Bi is similar to that observed for the triplet emission of Bi 3+ centers in some other hosts (see, e.g., [1,[9][10][11]). It can be described within the phenomenological model used in [1] for Bi 3+ centers in Y 3 Ga 5 O 12 .…”
Section: The Low-temperature Luminescence Decay Kinetics and The Quansupporting
confidence: 79%
“…Thus, the decay kinetics of the UV emissions of LuAG:Bi and YAG:Bi is similar to that observed for the triplet emission of Bi 3+ centers in some other hosts (see, e.g., [1,[9][10][11]). It can be described within the phenomenological model used in [1] for Bi 3+ centers in Y 3 Ga 5 O 12 .…”
Section: The Low-temperature Luminescence Decay Kinetics and The Quansupporting
confidence: 79%
“…Comparison of the data obtained for YAG:Bi in the present paper and for LuAG:Bi by Babin et al (2009) with those reported for the UV emission of Bi 3þ centers in other hosts (see, e.g., Wolfert and Blasse, 1985;Donker et al, 1989;Aceves et al, 1996;Nikl et al, 2005) allows us to conclude that the 5.9 eV and 4.57 eV excitation bands arise from the electronic transitions to the singlet and The intensity of the UV band is decreased 10 times. The spectra are distorted around 2.7 eV due to the contamination of the samples with Ce 3þ ions and the reabsorption of the VIS emission in the z2.7 eV absorption band of Ce 3þ centers.…”
Section: Ultraviolet Luminescencesupporting
confidence: 76%
“…Thus, emission decay of from A X -minimum can be decomposited into two (fast and slow) components. The lifetimes of the A X -slow components of ns 2 -ions luminescence usually are of the order of micro-and even milliseconds at room temperature in AHC [12,19] and oxides [20]. So, observed magnitude of lifetime equal to 0.4-0.8 ms for the Bi 3+ ions emission in CaWO 4 :Bi and CdWO 4 :Bi [4,5] crystals at 300 K is the typical lifetime for the A X -luminescence of ns 2 -ions.…”
Section: Article In Pressmentioning
confidence: 99%
“…The 3 P 0 and 3 P 1 states form a double minimum in the configurational space due to the Jahn-Teller effect, labeled as A T and A X , [11,12,19]. Because radiative de-excitation of the A T -minimum to the ground 1 S 0 state is parity allowed (due to j-j coupling), the emission decay is rather short (typically in nanosecond range for Tl + , Pb 2+ and Bi 3+ ions in Alkali-Halide compounds (AHC) [12,19]). Luminescence from A X -minimum is the superposition of two processes: the j-j allowed emission, related to the 3 P 1 -1 S 0 transition, and slow process, related to depopulation of the 3 P 0 meta-stable level (the 3 P 0 -1 S 0 transition is strongly forbidden).…”
Section: Article In Pressmentioning
confidence: 99%